Efficiency of air purifier (HEPA) in the control of microbial aerosol in a dental clinic - Lam, Carol O.
Dental procedures such as ultrasonic scaling and the use of handpiece have been known to produce great amount of microbial aerosol which when lodged into the lungs have been known to cause respiratory diseases. Dental personnel and patients are exposed to this environment everytime they come into the dental clinic. As an engineering control, air purifiers were used and have been found to effectively remove 99% of these aerosol 0.3 microns in diameter or larger. The aim of this study is to test the efficiency of an air purifier (HEPA) in controlling the level of microbial aerosol in a dental set-up. The results showed that there was an effective reduction in 60% of the microbial aerosol samples in the FAR location, whereas, there was 0% effective reduction of the microbial aerosol samples in the NEAR location. Also, regardless of the dental activity done, the effectiveness of the air purifier (HEPA) is the same.